Using the definitions of hyperbolic functions in terms of exponentials show that sech^2(x) = 1-tanh^2(x)

tanh(x) = ((ex-e-x)/2)/((ex+e-x)/2) 1 - tanh2(x) = 1-((ex-e-x)/(ex+e-x))2  = ((e2x+e-2x+2)-(e2x+e-2x-2))/(ex+e-x)2 = (2ex.2e-x)/(ex+e-x)2 = 4/(ex+e-x)2 = sech2x

Related Further Mathematics A Level answers

All answers ▸

Finding modulus and argument of complex number (x+iy)


You have three keys in your pocket which you extract in a random way to unlock a lock. Assume that exactly one key opens the door when you pick it out of your pocket. Find the expectation value of the number of times you need to pick out a key to unlock.


Show that the sum from 1 to n of 1/(2n+1)(2n-1) is equal to n/(2n+1) by Induction


Given a curve with parametric equations, x=acos^3(t) and y=asin^3(t), find the length of the curve between points A and B, where t=0 and t=2pi respectively.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences